1996
DOI: 10.2494/photopolymer.9.367
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Novel Asymmetric Biphenyl Type Polyimides.

Abstract: Asymmetric biphenyl type polyimides (PI) were prepared by thermal imidization of polyamic acids (PAA) derived from 2,3,3',4'biphenyltetracarboxylic dianhydride (a-BPDA) and p-phenylenediamine (PDA) or 4,4'-oxydianiline (ODA). The degrees of molecular orientation, film densities, and dynamic mechanical properties of these PIs were compared with those of familiar PIs based on symmetric 3,4,3',4'biphenyltetracazboxylic dianhydride (s-BPDA). PI(a-BPDA/PDA) cured at 350°C showed a Tg close to that of PI(s-BPDA/PDA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In contrast to this trend, we have previously reported that PI films derived from an isomer of s-BPDA, namely 2,3,3 1 ,4 1 -BPDA, with a bent/distorted structure, (asymmetric BPDA or a-BPDA, table 1) always led to higher T g values than the corresponding PIs from s-BPDA with the same diamines [8,11]. The increased T g values can be explained from the suppressed internal rotation around the biphenyl linkage in the a-biphenyldiimide (a-BPDI) moiety.…”
Section: Introductionmentioning
confidence: 68%
“…In contrast to this trend, we have previously reported that PI films derived from an isomer of s-BPDA, namely 2,3,3 1 ,4 1 -BPDA, with a bent/distorted structure, (asymmetric BPDA or a-BPDA, table 1) always led to higher T g values than the corresponding PIs from s-BPDA with the same diamines [8,11]. The increased T g values can be explained from the suppressed internal rotation around the biphenyl linkage in the a-biphenyldiimide (a-BPDI) moiety.…”
Section: Introductionmentioning
confidence: 68%
“…Ultraviolet−visible (UV−vis) absorption spectra of biphenyl derivatives provide qualitative information on the biphenyl conformation in solution; when ω ≈ 90°, the absorption spectrum becomes similar to the 2-fold spectrum of the corresponding monomeric unit (phenyl derivatives) owing to the sterically inhibited conjugation, but a peak red shift and enhancement of the band intensity become prominent as it approaches coplanar structure. , According to this criterion, we compared M(a-BPDA/CHA) with M(PA/CHA) as its monomeric derivatives, since the corresponding aniline (AN)-derived model compounds do not show a distinct peak of the (π,π*) band. , Figure shows the absorption spectra of these model compounds in solution, together with M(s-BPDA/CHA). M(a-BPDA/CHA) exhibited a stronger and red-shifted spectrum compared to the 2-fold of the M(PA/CHA) spectrum, suggesting qualitatively that a-BPDA has a ω lower than 90°.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the local ordering, which depends strongly on the manufacturing conditions, was observed by means of various techniques, and the role of the ordered structures for the properties was discussed. The most extensively reported results deal with the Kapton type polyimide, PMDA/ODA, derived from pyromellitic dianhydride (PMDA) and ODA. So far, we have focused Upilex type PIs, i.e., s-BPDA/PDA and s-BPDA/ODA, and reported the improved mechanical properties of the homopolymers , and their composites, , the spontaneous molecular orientation phenomenon induced by thermal imidization, , and local ordered structure formation. , However, there are few reports on asymmetric biphenyl type PIs, since this monomer is not commercially available. The present paper describes the properties of the new type of PIs derived from a-BPDA and discusses the comparison with the corresponding s-BPDA-based PIs. We focus here on the dynamic mechanical properties of a-BPDA-based homopolyimides and, in addition, the copolyimides and the blends containing a small content of a-BPDA component.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Tensile properties of typical PIs are given in Table V. Typically found were tensile strengths at break of ca.…”
Section: Properties Of Polymersmentioning
confidence: 99%